Pengelolaan Potensi Wisata di Daerah Otonom Bertumpu Kreativitas dan Inovasi Aparatur Pemerintah Daerah - Abdul Kholiq Azhari (Journal of Tourism and Creativity, 2019)
Abstract The natural beauty that exists in the autonomous region, in order to have added value, needs to be transformed creativity and innovativity into objects and tourist destinations of interest in tourists visit. The number of tourists visiting the existing tourist objects, open employment opportunities and the growth of tourism SMEs. The development of tourism SMEs as a form of peberdayaan people's economy in the economic system populist. For that the management of natural tourism potential into a competitive industry business, can meet the dynamics of the demands of tourists. Therefore, the cooperation of management of potential tourism objects, between the government apparatus with BUMN and Private, is a creative solution as an innovative breakthrough. Reorientation, refunctionalization and restructuring as well as determination of tourism village is an institutional innovation conducted by local government apparatus. Keywords: management, tourism, creativity, innovation, local government apparatus